About quantum holography and parallax: a physical interpretation of the reality concepts (Research, Society and Development, 2022)
This article aims to analyze the interpretation of reality based on the theory of quantum holography, understanding the physical concepts necessary to comprehend it. The theory of reality will be due, in this article, to five definitions, the fifth one being the object of focus: the holographic understanding of reality, which is characterized as the overcoming of the "duality of the thing and the non-thing" - which is based on the Hegelian dialectic applied to Plato's cave. For this, both works of physics, philosophy and law were studied, as well as loose works of literature segmented to the aforementioned subjects.